PENINGKATAN PRESTASI SISWA MELALUI PEMBINAAN TEKNIK ONE INPUT MANY OUT PUT DI SD NEGERI BARATAN BONDOWOSO TAHUN PELAJARAN 2018/2019: SD NEGERI BARATAN BONDOWOSO - CETY INDRAWATY (Mitra Pendidikan, 2021)
Based on previous year's experience in Academic and non-academic activities in Binakal District, they have never won overall champion at the District level. The cause is the lack of empowerment of the teaching staff at the author's school. In coaching activities only 16.7% of the 12 teachers in the school are involved. There are still 83.3% who have not been empowered by the teaching staff at the author's school. Data on the results of student achievement both in the academic and non-academic fields of the previous year, in commemorating the 71st Anniversary of Independence of the Republic of Indonesia in 2016, out of 16 competitions only 4 championships One way to improve student achievement in both academic and non-academic fields is through the guidance of the One Input Many Out Put Technique. The results of this effort showed a significant increase in student achievement, namely by involving 11 teachers as coaches of 13 educators, namely 85% empowered coaches. Based on the results above, it can be concluded that the coaching of the One Input Many Out Put technique is able to improve student achievement. at SD Negeri Baratan, Binakal District, Bondowoso Regency.